"CONTRASTIVE ANALYSIS OF POLITENESS STRATEGIES IN ENGLISH AND UZBEK" (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
This study explores the contrastive analysis of politeness strategies in English and Uzbek, examining how each language employs different communicative methods to maintain social relationships and mitigate face-threatening acts. Using Brown and Levinson’s politeness theory as a framework, the research compares the strategies employed in both languages, focusing on indirectness, mitigation, and the use of honorifics.